Hubungan Asupan Zat Gizi Makro dengan Siklus Menstruasi pada Remaja Putri SMK Negeri 2 Tuban - Ayuk Candra; Dwi Kurnia PS; Lilia Faridatul Fauziah (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Menstruation is the decay of the uterine wall or accompanied by bleeding due to the absence of fertilization. Menstrual cycle disorders are caused by several factors including stress, endocrine disorders, diet, nutritional status, nutrient intake, physical activity and sleep quality. The purpose of this study was to determine the relationship between macronutrient intake and menstrual cycle female adolescents of SMK Negeri 2 Tuban. Analytical research method with cross sectional approach. The sample in this study was adolescent girls of SMK Negeri 2 Tuban totaling 201 respondents, as samples randomited by simple random sampling echniquel. Independent variable of macronutrients and dependent variable of menstrual cycle. The analysis in this study used the spearmans correlation statistical test. The results showed that energy and carbohydrate intake was almost half normal at 47.3% and 43.8%. While the protein intake is mostly normal at 57.2% and fat intake is almost half experiencing excess intake at 44.3%. Statistical test results were obtained (p < 0.05), energy intake (p = 0.000), protein intake (p = 0.003), fat intake (p = 0.000) , and carbohydrate intake (p = 0.000). The conclusion of this study is that there is a significant relationship between macronutrient intake and menstrual cycle in adolescent girls of SMK Negeri 2 Tuban.